2020
DOI: 10.1108/jarhe-07-2018-0136
|View full text |Cite
|
Sign up to set email alerts
|

Empowering tertiary level students to solve their own study-related problems to improve study performance

Abstract: PurposeStudents’ progressing to tertiary (undergrad or higher) level education often faces problems due to the change in the educational settings that may directly or indirectly affect their studies and interim results. In addition, they may suffer from low self-esteem, which in turn may result from another set of issues such as negative peers, past poor results, unable to get into a school of choice and so on. Those who have to live away from home to attend a university could have their own set of problems. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
0
9
0
4
Order By: Relevance
“…That said, Meisalo et al (2002) found in a rural population in Finland that the complexity of programming course content in an engineering faculty, combined with problems of student comprehension, led to the dropout of part of the student population in the first year of training. Similarly, Nishat et al (2020) found that class difficulty expressed in content is often one of the reasons why rural students drop out.…”
Section: Academic Determinantmentioning
confidence: 95%
See 4 more Smart Citations
“…That said, Meisalo et al (2002) found in a rural population in Finland that the complexity of programming course content in an engineering faculty, combined with problems of student comprehension, led to the dropout of part of the student population in the first year of training. Similarly, Nishat et al (2020) found that class difficulty expressed in content is often one of the reasons why rural students drop out.…”
Section: Academic Determinantmentioning
confidence: 95%
“…In relation to personal obligations represented in domestic and household chores, unemployed adults tend to drop out due to the need to provide basic goods and services to their houses, leading them to limit their spending to cover these needs, reducing or eliminating investments in education, so that if the chief member of the family or any of his relatives is the one who studies, he has to drop out, due to the economic insecurity that exists in rural areas (Nishat et al, 2020;De Hart and Venter, 2013). In the case of the work obligations of rural students, research generally agrees that the hours allocated to work compete with study hours.…”
Section: Individual Determinantmentioning
confidence: 99%
See 3 more Smart Citations